Impacts of irrigation and hydroelectric power developments on the Victoria Nile in Uganda - Mutenyo, Isaac B. (Cranfield University, 2009)
This research aimed at increasing the understanding of the water resources of the Victoria Nile basin and assessing the impact of irrigation and hydropower developments on the Victoria Nile under different rainfall regimes. A Bayesian Network constructed with the HUGIN expert researcher software version 6.9 was used as the decision tool. The Network used a mixture of data, information from previous studies and consultation with experts/stakeholders. A network consisting of 21 nodes was developed and run to determine the impacts of different development scenarios. The Victoria Nile basin in Uganda is the first recipient of the river Nile flow as it leaves Lake Victoria. In this basin, there is potential for 5 large hydroelectric power plants and the basin consists of 70% of the irrigation potential in Uganda and yet it is one of the most lacking in hydrological data in the Nile basin. Further downstream of this basin are two riparian states, Egypt and Sudan which according to the prevailing legislation on the use of the Nile share amongst themselves the entire river flow. The research shows that Irrigation and hydropower developments have modest effects on lake levels and river flows exiting the basin. Rainfall occurrence on the other hand has the largest effect on the lake levels and Victoria Nile river flow exiting the basin. It is shown that in situations of very high water demand, which occurs when annual rainfall is less than 1,200 mm, full irrigation potential is utilized and all 5 hydroelectric power plants are developed, irrigation water need is not more than 7% of the Nile flow from the basin. The effects of hydropower plants are manifested mainly in the socioeconomic impacts in their vicinity, which are found to be large and to increase with the number of plants developed. The current mode of operation of outflows from Lake Victoria which is based on an international agreement between Uganda and Egypt is a satisfactory means of control only during moderate rainfall events and lake levels. However, for extreme conditions of lake levels outside the range of 10.8-11.6 m it is inadequate under increasing demands of hydroelectric power generation.